A critic of NEMA: Waste Act 59 of 2008, so many promises, little implementation and enforcement - Zhakata, E.; Gundani, S. R.; Chauke, V.; Odeku, K. O. (SAAPAM (South African Association of Public Administration and Management), 2016)
The study is focused on the management of Waste in South Africa by investigating and analysing the National Environmental Management Waste Act 59 of 2008. The current trends review that challenges have been noted on the interpretation and enforcement of the Act. The definition of Waste in the Act has been described as restrictive, which means it has been difficult to apply the act owing to the definition which excludes other types of Waste. The study will also expose the need for more corporative governance as far as waste management is concerned. The study will further interrogate how other jurisdictions define the term ‘Wasteʼ and South Africa's commitment to international instruments dealing with waste management and the need for sustainable development. The study will draw its focus from the Constitution, National Environmental Management Act and other instruments.
Article
Keywords: Environment; Environmental law; Waste; Waste management; Waste management; Environmental law; Refuse and refuse disposal; Waste disposal in the ground